2000
DOI: 10.1002/(sici)1097-4644(20000101)76:1<133::aid-jcb13>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the intracellular trafficking of two alternatively spliced isoforms of pp120, a substrate of the insulin receptor tyrosine kinase

Abstract: pp120, a substrate of the insulin receptor tyrosine kinase, is a plasma membrane glycoprotein in the hepatocyte. It is expressed as two spliced isoforms differing by the presence (full length) or absence (truncated) of most of the intracellular domain including all phosphorylation sites. Because the two isoforms differ by their ability to regulate receptor-mediated insulin endocytosis and degradation, we aimed to investigate the cellular basis for this functional difference by comparing their intracellular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…However, were the Lys residues mutated to three Ala residues a complete re-localization of CEACAM1-L to the apical surface occurred. These three Lys residues therefore play an important role in the steady state lateral localization of CEACAM1-L. Another important amino acid for CEACAM1-L intracellular transport and function, is Ser503 (Choice et al, 1999;Fournès et al, 2001) and thus we investigated its role in lateral localization of CEACAM1-L by changing it to Ala. This mutation resulted in the complete disappearance of CEACAM1-L from the lateral surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, were the Lys residues mutated to three Ala residues a complete re-localization of CEACAM1-L to the apical surface occurred. These three Lys residues therefore play an important role in the steady state lateral localization of CEACAM1-L. Another important amino acid for CEACAM1-L intracellular transport and function, is Ser503 (Choice et al, 1999;Fournès et al, 2001) and thus we investigated its role in lateral localization of CEACAM1-L by changing it to Ala. This mutation resulted in the complete disappearance of CEACAM1-L from the lateral surface.…”
Section: Resultsmentioning
confidence: 99%
“…Absence of an absolute requirement for N-linked glycosylation for transfer of S-D to the surface membrane has been shown in intestinal extracts [Danielsen and Cowell, 1986]. Similarly, complete glycosylation of the insulin receptor, of its close relative, the insulin-like growth factor receptor, and of one of its substrate, pp120, was not required for their insertion in the plasma membrane [Duronio et al, 1986;Choice et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…The S-D immunoprecipitates were boiled for 5 min in 150 mM sodium citrate, 2% SDS, pH 5.5, centrifuged at 15,000g for 5 min and treated with Endo-b-N-acetylglucosaminidase H (Endo H, Boehringer Mannheim Co.), as described previously [Choice et al, 1999]. Brie¯y, Endoglycosidase F/N-glycosidase F Endo H (10 mU) was added to the recovered supernatant, and the digestion mixture placed at 37 C for 1 h with a thin overlay of toluene.…”
Section: Treatment Of S-d By Endoglycosidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes are potential candidates for regulating epithelial-mesenchymal cell interactions in the human placenta. These genes are also expressed in the embryo and play major roles in embryonic development [78, 79]. Microarray expression profiling of placental trophoblast and endothelial cells revealed that novel placental homeobox genes TGIF, MEIS2E, LIM2 , and SMAP31-12 are also highly expressed in trophoblast cells (Murthi et al unpublished data).…”
Section: Homeobox Genesmentioning
confidence: 99%